1997
DOI: 10.1038/sj.onc.1200862
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of polo-like kinase (PLK) expression in non-small cell lung cancer

Abstract: Our previous data indicate that the expression of the PLK gene which codes for a serine/threonine kinase is restricted to proliferating cells. In Northern blot experiments PLK mRNA expression was at the limit of detection in normal lung tissue but elevated in most samples of non-small cell lung cancer (NSCLC). A very low frequency of PLK transcripts was only found in bronchiolo-alveolar carcinomas. NSCLC patients whose tumors showed moderate PLK expression survived signi®cantly longer (5 year survival rate=51.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
217
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 309 publications
(230 citation statements)
references
References 25 publications
12
217
0
1
Order By: Relevance
“…This hypothesis matches well with observations that PLK1 expression is a survival parameter in oesophageal carcinoma (Tokumitsu et al, 1999), lung carcinoma (Wolf et al, 1997) and squamous cell carcinoma of head and neck (Knecht et al, 1999), and serves as a marker for metastatic disease in malignant melanoma (Kneisel et al, 2002).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This hypothesis matches well with observations that PLK1 expression is a survival parameter in oesophageal carcinoma (Tokumitsu et al, 1999), lung carcinoma (Wolf et al, 1997) and squamous cell carcinoma of head and neck (Knecht et al, 1999), and serves as a marker for metastatic disease in malignant melanoma (Kneisel et al, 2002).…”
Section: Discussionsupporting
confidence: 89%
“…Studies on the expression of PLK1 have been performed on carcinomas of lung (Wolf et al, 1997), head and neck (Knecht et al, 1999), oesophagus and stomach (Tokumitsu et al, 1999), skin (Kneisel et al, 2002), breast , brain (Dietzmann et al, 2001), endometrium and ovary (Takai et al, 2001a, b). All studies consistently reported an overexpression of PLK1 in the respective tumour tissue compared to the corresponding nontransformed tissue of origin.…”
mentioning
confidence: 99%
“…No PLK expression has been detected in normal non-dividing cells but, similarly to cyclin B1, it is commonly over-expressed in human cancers (Holtrich et al, 1994). One study has shown elevated PLK mRNA expression in most NSCLC tumours and, similar to cyclinB1, high PLK expression has been associated with poor survival (Wolf et al, 1997). Consistent with previous findings, the majority of cases had a high expression of both CCNB1 and PLK.…”
Section: Up-regulated Genessupporting
confidence: 76%
“…A large number are derived from receptor genes, transcription factor genes, cell cycle related genes and genes implicated in chromatin structure. PLK1 can a ect chromosome number and chromosome segregation (Wolf et al, 1997), while overproduction of RanBP2 in yeast induces mitotic chromosome disjunction (Ouspenski et al, 1995). Elevated expression of both PLK1 and RanBP2 may a ect chromosome number and mitosis in CIN, thereby potentially contributing to chromosomal instability.…”
mentioning
confidence: 99%